The Representation of the Epic Time Concept in Yakut Olonkho and Turkic-Mongolian Epics of Siberia: Structural Models - Borisov, Yuriy Petrovich (Journal of History Culture and Art Research, 2018)
The relevance of this article is justified by the increasing interest in studying epic texts; in this regard, the problem of conceptual structure still requires some insight. The present study discusses a novel topic in which fixed formulas of epic TIME serve as the object of cognitive analysis. These fixed formulas have not yet been studied from the point of the EPIC TIME concept. The purpose of this research is to single out the concept structure of EPIC TIME in Yakut olonkho and Turkic-Mongolian epics of Siberia and to compare their universal and national features. The following sources served as the basis for the analysis: three olonkho texts, which represent the main regions where the Yakut epics take place and A Guide of Typical Heroic Epic Locations of the Peoples of Siberia by E.N. Kuzmina. The study of the concept structure of EPIC TIME was achieved using the method of singling out lexicographic definitions of the epic formula components in the macro-context. Implementing the method of structural modeling in the research, models of concept structures which form the basis of the epic TIME semantic formulas were singled out. The temporal concept structure is based on the rhythmic and syntactic parallelisms and literal repetitions in the epic TIME formulas. The correlation of rhythmic and syntactic parallelisms and literal repetitions helps to explain the aspects of epic TIME. The singled out concept structures are further compared using the concept analysis method. Having analyzed the definition to the concept of EPIC TIME in Yakut olonkho and Turkic-Mongolian epics of Siberia, it became apparent that there is a convergence between the two epics on the grammatical level of analysis. However, there are also instances of implicit differences in the analyzed concepts. These instances are located in the deep structure of the concepts. First of all, TIME measurement units do not coincide with each other; secondly, the initial storyline points and the directiveness of the EPIC TIME do not match; thirdly, the secondary and indirect attributes, which assist in positioning the EPIC TIME, do not coincide.